Marketing Mix Strategy in Efforts to Increase Drug Sales at the Healthy Pharmacy in Gunungsitoli City, Produced by PT Kalbe Farma Tbk - Waruwu, Frisca Angela; Zebua, Emanuel; Zalukhu, Yuterlin; Harefa, Idarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research is motivated by business developments which require every entrepreneur to combine marketing mix functions so that the company's business can run smoothly. Many argue that marketing should play an important role in determining the direction of a company's concept and strategy. This research aims to determine the marketing mix strategy in an effort to increase drug sales in healthy pharmacies in Gunungsitoli City. This research is a descriptive study with a qualitative approach with the research object being a healthy pharmacy in Gunungsitoli City. Data sources were taken from documentation, interview results and observation results. In this research, interviews with various questions about the research topic were conducted directly. The results of this research show that the healthy pharmacy in Gunungsitoli City has implemented the 7p marketing mix strategy in its business which has been running but is still not optimal/deficient and this has resulted in a decline in sales due to lack of promotion and increasingly tighter competition. Therefore, implementing the marketing mix strategy is able to increase sales volume.